Determinan Perilaku Beli Hijau pada Generasi Z Dimoderasi Pengetahuan Lingkungan - Wahyu Dian Mawarni; Waluyo Budi Atmoko; Ariefah Yulandari (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
This study examines the effects of social influence, environmental concern, subjective norm, and perceived green behavioral control on green purchase intention, the effect of green purchase intention on green purchase behavior, and the moderating role of environmental knowledge in the intention-behavior relationship. A quantitative approach with a two-wave longitudinal survey was employed. The sample comprised 102 Generation Z respondents in Indonesia selected through purposive sampling. The first wave measured the determinants of green purchase intention and environmental knowledge. One week later, the same respondents were contacted to record the actual purchase of a stainless-steel tumbler. Data were analyzed using multiple linear regression, binary logistic regression, and moderation analysis with 1,000 bootstrap replications. Social influence, environmental concern, and subjective norm did not significantly affect green purchase intention, whereas perceived green behavioral control had a positive and significant effect. Green purchase intention positively and significantly affected green purchase behavior. Environmental knowledge strengthened the relationship between intention and behavior, as indicated by an interaction significance of p = 0.047 and an increase in Nagelkerke R-squared to 0.196. The findings indicate that perceived ability, purchasing convenience, and environmental knowledge are more decisive in realizing green purchases among Generation Z than general social pressure and environmental concern.